Management control systems on managing employees and its effect on performance in services sector / Maziana Zakaria - Zakaria, Maziana (Institute of Graduate Studies, UiTM, 2016)
Management control systems (MCS) were regarded as a helpful tool for organization in terms of controlling employees due to its nature dealing with resources and capabilities. Employees, currently, have become the central part in sustaining competitive advantage which has been argued that have a significant impact on performance. Employers are constantly searching for more relevant approaches in managing employees to achieve utmost performance, whilst employees are keen to enhance the benefits at work such as opportunities for more absorbing and inspiring work patterns. Therefore, the main objective of this study was to examine the nature of employees control as the elements of MCS on performance and the influence of task environment on MCS in services sector. Further consideration of wellbeing will take place as moderator in the relationship of MCS and performance. As such, this model eventually leads to having better on-going decision making. The employees control was incorporated in general MCS (omcs), interactive control (mics) and enabling control (mecs) systems as the elements of MCS. A questionnaire survey was conducted among managers in services organization which located in Peninsular Malaysia. An analysis of 166 survey responses shows mixed results for the hypotheses developed which empirically tested using Partial Least Square-SEM. For direct relationship, the results revealed that there is significant positive relationship between task environment and MCS…